International Value-Added Linkages in Development Accounting - Alejandro Cu\~nat; Robert Zymek (Center for Economic Studies and ifo Institute (CESifo), 2018)
We generalise the traditional development-accounting framework to an open-economy setting. In addition to factor endowments and productivity, relative factor costs emerge as a source of real-income variation across countries. These are shaped by bilateral trade determinants (which underpin the patterns of “international value-added linkages”) and the global distribution of factor endowments and final expenditures. We use information on endowments, trade balances and value-added trade to back out the relative factor costs of 40 major economies in a theory-consistent manner. This reduces the variation in “residual” productivity required to explain the observed per-capita income differences by more than one half.
Keywords: E01; F15; F40; F62; F63; 330; world input-output; development accounting; productivity